Hubungan Nyeri Punggung Bawah dengan Kualitas Tidur Pasien Low Back Pain (LBP) di Rumah Sakit Awal Bros Pekanbaru - Alfina Damayanti; Tutik Rahayu; Hernandia Distinarista (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: “The highest prevalence of LBP at Awal Bros Hospital in Pekanbaru is estimated to be 0.70% or 3,238 people in 2022, 1.38% or 5,584 people in 2023, and 2,084 people or 1.11% in 2024. The impact of low back pain can make movement difficult, affect quality of life, and limit work activities and mental health. Method: The design of this research is quantitative research, with a cross sectional approach. The sampling technique used the consecutive formula and the sample size was 83 respondents. The data collection method uses a questionnaire. The data analysis used is univariate analysis and bivariate analysis using Somer's test. Results: Characteristics of the majority of respondents were women, 51 people (61.4%), 60 people aged > 35 years (72.3%), 54 people with a working period of > 5 years (65.1%), with BMI obesity amounted to 49 people (59.0%), amounted to 53 people (63.9%) who never did physical activity (exercise per week). The majority experienced moderate lower back pain, amounting to 34 respondents (41.0%), and had poor sleep quality, amounting to 51 respondents (61.4%). Based on the analysis test results, the d value was 0.482, meaning there was a moderate positive correlation with the p value (0.000 < 0.05), meaning there was a relationship between lower back pain and sleep quality in LBP patients at Awal Bros Hospital, Pekanbaru. Conclusion: There is a relationship between lower back pain and sleep quality. This shows that the higher the lower back pain, the worse the sleep quality.”